A description of clinical characteristics and treatment patterns observed within prescribed opioid users in Germany and the UK. (July 2014) - Chevalier, Pierre; Smulders, Maartje; Chavoshi, Soheil; Sostek, Mark; LoCasale, Robert
SUMMARY : Aims : To describe a cohort of new opioid users (adult noncancer patients) in terms of clinical characteristics and treatment patterns in the UK and Germany.Material & methods : Data used were extracted from electronic medical records databases (UK: Clinical Practice Research Database-Hospital Episode Statistics; Germany: IMS Disease Analyzer) covering the 2008–2012 period.Results : Most eligible patients were treated with opioids for less than 6 months (UK: 78.7% and Germany: 93.7%) and indexed on weak opioids (UK: 89.5% and Germany: 88.6%). Most prescribed opioids were codeine (UK) and tramadol (Germany). Most prevalent comorbidities were dorsalgia/depression. Constipation was observed in 16.8%/17.4% (UK/Germany) of chronic users (>6 months).Conclusion : While both populations were highly morbid populations largely initiated on weak opioids, chronic use was less common in Germany.